Processos e feições geomorfológicas na faixa de dobramentos sergipana do domínio Vaza-Barris - Lima, Luana Pereira (2022)
The reading of the landscape in the geomorphological conception, besides being dynamic, represents the interaction between the physical, biotic, and anthropic components. It is, therefore, an inheritance of processes that have acted over time, structurally conditioning the incidences on the forms and, from climatic variations, intensifying and typifying wear and modeling. Various genetic and evolutionary geomorphological theories and approaches have assisted in the interpretation of the polygenetic landscape and current morphology of the VazaBarris Domain. The research aimed to analyze the evolutionary processes in the geomorphological dynamics of the landscape of the Vaza-Barris Domain, taking into consideration the interactive nature of the environmental components in conditioning morphogenesis, morphodynamics, and morphosculture. To fulfill the objectives during the investigation, the General Systems Theory was used as a methodological approach articulated with the proposal elaborated by Libout (1971), which defines the four levels of geographic research and directs the steps in a comprehensible sequence for the presentation of the results. In general terms, the research consisted of the compilation of existing data and the acquisition of new data, the treatment and interpretation of the data necessary to elucidate the facts, the systematization of the results, and the conclusive synthesis. The methodological procedures in distinct phases followed the compilatory, correlative, semantic, and normative levels. The physical-natural elements that condition the relief are expressed in the landscape of the VazaBarris Domain through the geology, marked by folds and fractures from the shear zones; of the climate, classified as humid coastal, sub-humid transitional, and semi-arid; of the soil types that range from incipient to well developed; and of the vegetation cover, which varies from ombrophilous to seasonal. The extracted morphometric and morphostructural indexes revealed the intensity of the action of the drainage network in consonance with the structure, culminating in the denudation and differentiation of the relief of the Vaza-Barris Domain. The analysis of the conditioning factors and indices, resulted in the geomorphological compartmentalization, being identified the morphostructure Remnant of the Fold Roots; the Minor Plateaus adjacent geomorphological region to the Tucano-Jatobá Basin; and the Dissected Plateaudo Vaza-Barris geomorphological unit. In fourth order of magnitude, accumulation modeling (Colluvium Ramps) were identified; dissolution (Karst Hills, Karst Ridge and Poljer); flattening (gently undulating Flattened Surfaces, partially preserved Flattened Surfaces and Pedestrian Ramps); and dissection (Low Hills, Residual Hills, Dissected Surfaces on Hills and Structural Features, Dissected Surfaces on Metacalcary, Dissected Surfaces on Hills, Dissected Surfaces on Hills and Low Hills, Dissected Tablelands and Structural Valleys). Conclude, therefore, that the geomorphology of the Vaza-Barris Domain evolved from successive phases and resumption of erosion, associated to weathering and processes derived from climatic changes, structural controls and environmental conditioning, resulting in diversified relief units along its extension.